In Vitro Antibacterial Activities of Noni Fruit (Morinda citrifolia L.) Ethanolic Extract against Escherichia coli and Salmonella typhimurium - Andi Mus Malikah; Fuji Astuty Auza; Andi Murlina Tesse; Nur Santy Asminaya; Astriana Napirah (Chalaza Journal of Animal Husbandry, 2022)
This research aimed to examine the in vitro antibacterial activity of noni fruit extract (NE) against the growth of Escherichia coli and Salmonella typhymurium bacteria. The study was carried out for 3 weeks from April to May 2022. The study used Completely Randomized Design (CRD) which consisted of 6 treatments and each treatment was replicated 3 times so that there were 18 experimental units. The treatments used were: P1 = 5% NE concentration P2 = 15% NE concentration, P3 = 25% NE concentration, P4 = 35% NE concentration, P5 = NE concentration 45%, and P6 = 55% NE concentration. The parameters observed in this study were the physical characteristics of noni fruit extract and its antibacterial activity. The results of the study showed that noni fruit extract had a significant effect (P0.05) on the growth of Escherichia coli and Salmonella typhymurium bacteria. A concentration of 55% was the most effective concentration in inhibiting the growth of the two tested bacteria.